Pirfenidone for idiopathic pulmonary fibrosis: analysis of pooled data from three multinational phase 3 trials. Issue 1 (January 2016) - Noble, Paul W.; Albera, Carlo; Bradford, Williamson Z.; Costabel, Ulrich; du Bois, Roland M.; Fagan, Elizabeth A.; Fishman, Robert S.; Glaspole, Ian; Glassberg, Marilyn K.; Lancaster, Lisa; Lederer, David J.; Leff, Jonathan A.; et al.
Pirfenidone is an antifibrotic agent that has been evaluated in three multinational phase 3 trials in patients with idiopathic pulmonary fibrosis (IPF). We analysed pooled data from the multinational trials to obtain the most precise estimates of the magnitude of treatment effect on measures of disease progression. All patients randomised to pirfenidone 2403 mg·day −1 or placebo in the CAPACITY or ASCEND studies were included in the analysis. Pooled analyses of outcomes at 1 year were based on the pre-specified end-points and analytic methods described in the ASCEND study protocol. A total of 1247 patients were included in the analysis. At 1 year, pirfenidone reduced the proportion of patients with a ≥10% decline in per cent predicted forced vital capacity or death by 43.8% (95% CI 29.3–55.4%) and increased the proportion of patients with no decline by 59.3% (95% CI 29.0–96.8%). A treatment benefit was also observed for progression-free survival, 6-min walk distance and dyspnoea. Gastrointestinal and skin-related adverse events were more common in the pirfenidone group, but rarely led to discontinuation. Analysis of data from three phase 3 trials demonstrated that treatment with pirfenidone for 1 year resulted in clinically meaningful reductions in disease progression in patients with IPF. Treatment with pirfenidone for 1 year results in clinically meaningful reductions in IPF disease progression http://ow.ly/StvBk